The Firstborn Laestadians and the sacraments: Conceptual analysis as an approach to answering the question of why the Firstborn in Finland began administering the sacraments - Ollilainen, Anssi (Approaching Religion, 2020)
Firstborn Laestadians represent one branch of the Laestadian revival movement following the so-called Great Division of around the turn of the twentieth century. This article examines two concepts; ‘the priesthood of all believers’ and ‘the preacher’, which are used by adherents of Firstborn Laestadianism (FBL) to elucidate the further schism which took place in 2014–16 between the Firstborn and the Evangelical Lutheran Church of Finland (ELCF). Both concepts are to some extent contrasted with comparable ideas in Martin Luther’s (1483–1546) and Lars Levi Laestadius’s (1800–61) thinking, because Luther and Laestadius are held in high esteem by the Firstborn.